1982
DOI: 10.1111/j.1744-7976.1982.tb01987.x
|View full text |Cite
|
Sign up to set email alerts
|

Rural Farmer Productivity in the Tropics: The Nigerian Experience

Abstract: The dilemma posed by the poverty and low agricultural productivity of rural farmers in tropical countries in spite of generous natural resource endowments has continuously baffled their agricultural policy makers. This paper contends that this perplexing situation has been due primarily to the omission of a crucial determinant —producer's health capital — in the usual agricultural development models applied to these countries. This contention is analyzed through a deterministic model designed to relate rural … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Therefore, farming activities exposed workers to hazardous assortment which subsequently leads to paces of injuries and ailments. Ngambeki & Ikpi (1982) and Arcury et al, (2010) claimed that hazards are causing those who are actively involved in agricultural production not to make maximum use of all the inputs at their disposal, decreasing productivity and negatively impacting farm income rates. Injured agricultural workers are of no use especially to private organisations, their appointments are terminated.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, farming activities exposed workers to hazardous assortment which subsequently leads to paces of injuries and ailments. Ngambeki & Ikpi (1982) and Arcury et al, (2010) claimed that hazards are causing those who are actively involved in agricultural production not to make maximum use of all the inputs at their disposal, decreasing productivity and negatively impacting farm income rates. Injured agricultural workers are of no use especially to private organisations, their appointments are terminated.…”
Section: Introductionmentioning
confidence: 99%
“…A study in Nigeria, for example, found that the vast majority of women farmers practicing mixed cropping system suffered from intense muscular fatigue, heat exhaustion, and skin disorders, forcing them to take days off from attending to their crops [9]. Ngambeki & Ikpi stated that these hazards make farmers not to utilize fully all inputs at their disposal, reduces productivity, and equally impacts negatively on farm profit levels [10]. This study was therefore borne out of the need to ensure that farmers, most especially small scale farmers, in the study area become aware of the potential effects of farm hazards on agricultural productivity.…”
Section: Introductionmentioning
confidence: 99%